Control System in a Hybrid Solar Dryer - Reyes-Salinas, A; Cubillos-Montecino, F; Mahn-Osses, A; Vasquez-Fajardo, J (IEEE Computer Society, 2014)
Drying is one of the most energy-intensive processes in agro-products industry; for this reason using solar energy appears as an attractive not polluting alternative to be used in drying processes. However the daily and seasonal fluctuations in the radiation level requires using energy accumulators with phase change materials (paraffin wax), to have a continuous drying processes. In hybrid solar dryers with energy accumulation system, a control system is essential to coordinate the control valves that allow the income of air that comes from the solar panel or from the energy accumulator. In this work we implemented an advances multivariable control system that uses fuzzy logic in the hybrid solar dryer. The dryer includes an energy accumulator panel with paraffin wax as phase change material. The input variables were ambient temperature and solar radiation, both not controllable. The controlled variables were the opening level of the solar panel and accumulator energy valves. The control program consisted in an algorithm implemented with the Fuzzy toolbox in Matlab. Data were acquired with OPTO 22. The control system performed adequately, by closing or opening the respective valves as a response to the variations of solar radiation and ambient air temperature. This system will allow optimizing the use of solar energy. © 2014 IEEE.